2018
DOI: 10.1186/s12919-018-0144-7
|View full text |Cite
|
Sign up to set email alerts
|

Epigenome wide association study of SNP–CpG interactions on changes in triglyceride levels after pharmaceutical intervention: a GAW20 analysis

Abstract: In the search for an understanding of how genetic variation contributes to the heritability of common human disease, the potential role of epigenetic factors, such as methylation, is being explored with increasing frequency. Although standard analyses test for associations between methylation levels at individual cytosine-phosphate-guanine (CpG) sites and phenotypes of interest, some investigators have begun testing for methylation and how methylation may modulate the effects of genetic polymorphisms on phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
2
1
0
Order By: Relevance
“…Gombojav et al identified in more than 8000 Korean individuals, several functional loci in 11q23.3 and found that SIDT2 is associated with an effect on plasma TG levels [ 14 ]. These data are consistent with the findings from Moon et al, who carried out a multiple genotype-phenotype association study in more than 10,000 Korean subjects and identified that the variant rs1784042 was associated with MetS and its components [ 16 , 52 ]. In addition, Kulminsky et al in a GWAS with more than 26,000 individuals from five longitudinal studies identified that the rs1784042 variant was associated with TC levels [ 17 ].…”
Section: Discussionsupporting
confidence: 92%
“…Gombojav et al identified in more than 8000 Korean individuals, several functional loci in 11q23.3 and found that SIDT2 is associated with an effect on plasma TG levels [ 14 ]. These data are consistent with the findings from Moon et al, who carried out a multiple genotype-phenotype association study in more than 10,000 Korean subjects and identified that the variant rs1784042 was associated with MetS and its components [ 16 , 52 ]. In addition, Kulminsky et al in a GWAS with more than 26,000 individuals from five longitudinal studies identified that the rs1784042 variant was associated with TC levels [ 17 ].…”
Section: Discussionsupporting
confidence: 92%
“…We identified several associations for CpG methylation in SCD, FADS1/2, SLC7A11, TXNIP, and PHGDH with PUFAs. However, in line with previous studies, those in the FADS region appear to have a complex (epi)genetic architecture [37,[67][68][69][70]. The only CpG site showing associations with PUFAs, and additionally with the respective gene transcript, metabolic measure ratios, and disease endpoints was cg16246545 in PHGDH.…”
Section: Discussionsupporting
confidence: 87%
“…The variance explained by the model increased by 36% after adding the interaction between rs911847 ( SOD2 ) and cg24223887 (gene unknown) (results not shown). Published epigenome-wide studies have reported DNA methylation modulating the genetic impact on cardiovascular disease-related traits ( Veenstra et al, 2018 ; Wang et al, 2021b ) and type II diabetes ( Vohra et al, 2020 ), whereas for newborn telomere length, the current study is to our knowledge the first to identify SNP-CpG interactions.…”
Section: Discussionmentioning
confidence: 88%